HOW MANY LOBSTERS ARE IN THE SEA? - Enns, Ernest; Smith, Bruce (Image Analysis and Stereology, 2011)
A lobster fishery must have a reasonable estimate of the number of lobsters within the fishery in order to regulate the annual harvest. Stereological sampling procedures are used to estimate the number of lobsters in a defined region of the sea. From a given point in the fishery, a selective sample in a random direction to the boundary of the fishery is taken. This is repeated to generate a systematic sample from which the total population is estimated.